Olfactory change detection - Menzel, Susanne; Hummel, Thomas; Schäfer, Laura; Hummel, Cornelia; Croy, Ilona (Biological psychology, 2019)
•The olfactory system is assumed to be in a “constant state of change-blindness”.•We investigated the human capacity to detect changes in the olfactory environment.•Olfactory changes were reliably detected by only 18% of the subjects.•Those were characterized by high subjective importance of olfaction.•We conclude that olfaction is imprecise in guiding environmental change detection. The human olfactory system is characterized by poor temporal and spatial resolution. When determining changes in the environment, humans rather rely on visual than on olfactory information. Against this background, we developed a test in order to investigate the human capacity to detect changes in the olfactory environment and to determine potential modulators of olfactory change detection. Participants consecutively received four odors (2 odor qualities in 2 concentrations each) which were presented via a computer-controlled olfactometer. The participants’ task was to react as soon as they perceived a change of the odor. For control purpose, the same paradigm was also presented with visual instead of olfactory stimuli. A total of 83 healthy participants (aged 18–34 years, 50 women) were included; all of them were screened for attention, olfactory function, chemical sensitivity and the subjective importance of the sense of smell. While visual changes were detected above chance by all participants, olfactory changes were reliably detected by only 24% of the participants. Those were characterized by high subjective importance of olfaction and low chemical sensitivity. Across all participants, changes of olfactory quality were detected more frequently than changes of olfactory concentration. These results suggest that olfaction is imprecise in guiding environmental change detection and may help to explain why humans typically rate the importance of vision higher than the importance of olfaction.